The Dreadnought of the Air - Westerman, Percy F. (Percy Francis), 1876-1959 (Salt Lake City, UT : Project Gutenberg, 2014)
"(3z(BThe Dreadnought of the Air(3y (Bby Percy F. Westerman is a novel written in the early 20th century. The story centers around Sub-Lieutenant Basil Dacres, a young naval officer who finds himself embroiled in a series of adventures involving a mysterious airship. The book combines elements of naval fiction with emerging aviation themes, showcasing Dacres$1 (Bjourney and interactions against the backdrop of military life and intrigue." "At the start of the narrative, we are introduced to Dacres, a spirited young officer aboard H.M.S. "Royal Oak" moored near Singapore. His demeanor is light-hearted, characterized by practical jokes, but he faces serious repercussions after a prank that leads to his resignation from the Navy. As Dacres departs his ship and grapples with his uncertain future, he becomes intrigued by reports of a peculiar airship that seems to have eluded detection across various cities in England. The chapter sets the stage for the unfolding mystery and adventure surrounding Dacres as he navigates not only the challenges of his dismissal but also the thrilling possibility of engaging with the enigmatic world of airships." (This is an automatically generated summary.)s
Release date is 2014-06-27
Produced by R.G.P.M. van Giesen
Keywords: War stories; Airships -- Juvenile fiction